Professionalism in the Early Years - Miller, Linda, 1954-; Cable, Carrie (London : Hodder Education, 2008)
This is a groundbreaking text reflecting the government's new workforce agenda for the Early Years sector; written for students and practitioners to develop their knowledge and understanding of professional practice at Foundation Degree and Undergraduate level.
Includes bibliographical references and index.
Keywords: Early childhood teachers; Early childhood teachers -- Professional ethics; Early childhood education; Education